ANALYSIS OF FINANCIAL MANAGEMENT AND REPORTING AT THE BAUBAU LEGAL ASSISTANCE AND MEDIATION INSTITUTION - Fajar Rakasiwi Syamsuddin (SEAN Institute, 2023)
This study aims to determine the management and financial reporting in the offices of Baubau legal aid and mediation institutions. The sample for this research is reports on sources and uses of the budget and financial reports of the Baubau Legal Aid and Mediation Institute for 2021. The reason for choosing this is because the application of ISAK 35 concerning financial statements of non-profit organizations will become effective on January 1, 2020. The data analysis method used is analysis descriptive, namely by explaining in detail the events or facts that occur on the object of research. The results of the research show that financial management at LHBM Baubau, both the source and use of the funds, has been carried out in a transparent and accountable manner because it has followed the SOP and AD/ART that exist in LHBM Baubau. Besides that, financial reporting in Baubau LHBM still follows the type and format of profit-oriented entity financial statements and is not in accordance with the type and format as stipulated in ISAK 35 concerning financial statements of non-profit entities.